Implementasi Nilai-Nilai Sila Keempat Pancasila Mengenai Kebebasan Berpendapat pada Kegiatan Karang Taruna(Studi Kasus di Desa Jumapolo Kecamatan Jumapolo tahun 2016) - Putri, Dewanti Andriana, Dra. Hj. Sri Arfiah, S.H, M.Pd (2016)
This study aims to determine, the implementation of the values of fourth principle of Pancasila regarding freedom of speech, difficulties in implementing the values of fourth principle of Pancasila regarding freedom of expression, as well as solutions to overcome the obstacles in the implementation of the values of fourth principle of Pancasila regarding freedom of speech through the Youth organization in Jumapolo District of Jumapolo 2016. This research is descriptive research with qualitative approach that aimed to portray accurately the properties of the individual and social circumstances that arise in the community to serve as an object of research. The study was conducted in the District Youth organization Jumapolo Year 2016. The results of this research are: 1) Youth provides the opportunity for all group members Youth Organization to submit proposals or constructive suggestions for the progress of Youth Organization and all the other members respond positively, as well as any problems in the group Youth solved by consultation consensus. 2) Members of the Youth objected to the decision of the chairman of the Youth which tend to impose his own will and many members of the Youth who have not dared to express advice, suggestion or opinion in public in the activities of these meetings. 3) Provide guidance to the members of the Youth in order to express an opinion in public. Chairman of the Youth and other members of the Youth must receive good advice expressed his order the next regular activities Youth Youth members dared express an opinion. Keywords: implementation values pancasila, freedom of opinion, youth organization